Working for Nothing: Personality and Time Allocation in the UK - Marina Della Giusta; Sarah Jewell (Institute of Labor Economics (IZA), 2021)
We contribute to the literature on the effects of personality traits on labour market outcomes focusing on time mismanagement as an underlying mechanism. We document differences in time allocation to the labour market by different personality types in the UK and show how they may account for some of the labour market disadvantage experienced by more neurotic types (and the advantage experienced by more conscientious types) focussing in particular on unpaid overtime. We make use of the first ten waves of the Understanding Society Survey and show that particular personality types are more prone to working longer hours and experiencing time pressures. Whilst the effect of most personality traits is consistent with a rational theory of time allocation, we also find that neuroticism is instead associated with inconsistent behaviour (working fewer paid and more unpaid hours) and discuss implications for both labour market discrimination and labour supply theory.
Keywords: A13; D01; J22; Z1; 330; labour supply; overtime; time; time allocation; personality